Sistem Informasi Manajemen Rumah Sakit Di Instalasi Rawat Jalan Berdasarkan Metode Human, Organization, Dan Technology Di Rsud Dr. M.M. Dunda Limboto - Lilis Handayani; Bilondatu, Maimun (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2024)
Based on the human aspect, namely outpatient registration officers only understand the Hospital Management Information System through information technology officers, the organizational aspect is that there has been no evaluation of the use of the Hospital Management Information System and the implementation of the Hospital Management Information System as a whole, and officers who use the Hospital Management Information System only conduct training once after socialization, and seen from the technology aspect there are obstacles in the form of slow internet connections with internet access speeds of 500 Mbps to 1 GB coupled with the number of internet access users resulting in services in the outpatient unit sometimes experiencing delays in registration. The purpose of this study was to determine the description of the Hospital Management Information System in the outpatient installation based on the Human, Organization and Technology Methods. This type of research is quantitative with a cross-sectional design. This research was conducted at Dr. M. M. Dunda Limboto Hospital in June with a sample size of 30 people. The description of the Hospital Management Information System in the outpatient installation based on the Human, Organizational, and Technology methods at Dr.M.M Dunda Limboto Hospital obtained the results of 30 people (100%) officers who used the Hospital Management Information System in the good category and 0 people (0%) officers who used the Hospital Management Information System in the less category. Research suggestions include conducting surveys for Hospital Management Information System applications periodically to improve aspects of human, organization and technology methods.